Does evidence support the use of mobile phone apps as a driver for promoting healthy lifestyles from a public health perspective? A systematic review of Randomized Control Trials. Issue 12 (December 2017) - Covolo, L.; Ceretti, E.; Moneda, M.; Castaldi, S.; Gelatti, U.
Highlights: Health apps may encourage people to take more responsibility over their health and promote health behavior change over time. Considering the large use of health apps, it is essential for health professionals to understand how to use these tools in health interventions. RCTs with large samples and long follow-up are needed to analyse usefulness and efficacy of apps in health promotion. Abstract: Objective: The aim of this systematic review was to find a scientific evidence on the efficacy of apps in promoting healthy lifestyles. Methods: The research was carried out according to PRISMA Statement. Pubmed, Embase and Google Scholar searches were carried out up to September 2016 focusing on randomized control trials (RCTs). Results: Forty RCTs were selected. Most of the studies targeted weight management, PA and healthy eating (N = 35). A few RCTs focused on apps designed to sun protection, smoking cessation and alcohol consumption (N = 5). Only 10 RCTs (25%) found statistical difference between intervention and control groups for all the outcomes measured. Most of the studies had a short follow-up (65%, less than 6 months) and half of them a very small sample size (fewer than 100 subjects). Conclusion: Overall, the evidence so far showed a modest efficacy of apps in health promotion. Practice implications: There is a need to improve the overall quality of intervention studies focused on mobile apps in order to understand if they could became a valuable tool in support of health professionals and their efforts to promote education and health.